Association between Sasang constitutional types with obesity factors and sleep quality - Tae Yeong Kim; Sung Eun You; You Sun Ko (Integrative Medicine Research)
Background: The purpose of this study was to investigate differences in obesity factors according to Sasang constitutional types and quality of sleep among Korean female college students. Methods: Surveys using Sasang-types questionnaires(QSCCⅡ) and quality of sleep questionnaires(PSQI; Pittsburgh Sleep Quality Index) were conducted with 339 Korean female college students. Additionally, obesity factors, including weight, fat mass, fat percent, abdominal fat percent, body mass index (BMI) and obesity rates were measured. All data analyses were performed using one-way ANOVA and two-way ANOVA. Results: The interaction between Sasang types and quality of sleep was presented in the quality of sleep status, subjective quality of sleep (domain 1), sleep duration (domain 3) and sleep disturbance (domain 5). Variables with interaction effects had significant differences in terms of obesity factors between groups with different quality of sleep according to the Sasang types. Moreover, significant differences in obesity factors between different Sasang types according to the quality of sleep were also observed. Conclusion: This study characterized the reduction effect of improvement in quality of sleep on the fat mass of So-Yang type individuals and obesity factors in Tae-Eum type individuals. The results of this study will be used in improving sleep quality according to the Sasang types. Keywords: Korean female college students, Sasang constitutional types, Quality of sleep, Obesity factors, Interaction effect